The Light Intermediate Chain 2 Subpopulation of Dynein Regulates Mitotic Spindle Orientation - Sagar Mahale (Nature Portfolio, 2016)
Abstract Cytoplasmic dynein 1 is a multi-protein intracellular motor essential for mediating several mitotic functions, including the establishment of proper spindle orientation. The functional relevance and mechanistic distinctions between two discrete dynein subpopulations distinguished only by Light Intermediate Chain (LIC) homologues, LIC1 and LIC2 is unknown during mitosis. Here, we identify LIC2-dynein as the major mediator of proper spindle orientation and uncover its underlying molecular mechanism. Cortically localized dynein, essential for maintaining correct spindle orientation, consists majorly of LIC2-dynein, which interacts with cortical 14-3-3 ε- ζ and Par3, conserved proteins required for orienting the spindle. LIC2-dynein is also responsible for the majority of dynein-mediated asymmetric poleward transport of NuMA, helping focus microtubule minus ends. In addition, LIC2-dynein dominates in equatorially aligning chromosomes at metaphase and in regulating mitotic spindle length. Key mitotic functions of LIC2 were remarkably conserved in and essential for early embryonic divisions and development in zebrafish. Thus LIC2-dynein exclusively engages with two major cortical pathways to govern spindle orientation. Overall, we identify a novel selectivity of molecular interactions between the two LICs in mitosis as the underlying basis for their uneven distribution of labour in ensuring proper spindle orientation.